2022
DOI: 10.1038/s41418-022-00988-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle regulation: p53-p21-RB signaling

Abstract: The retinoblastoma protein RB and the transcription factor p53 are central tumor suppressors. They are often found inactivated in various tumor types. Both proteins play central roles in regulating the cell division cycle. RB forms complexes with the E2F family of transcription factors and downregulates numerous genes. Among the RB-E2F target genes, a large number code for key cell cycle regulators. Their transcriptional repression by the RB-E2F complex is released through phosphorylation of RB, leading to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
231
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(320 citation statements)
references
References 85 publications
(166 reference statements)
11
231
1
Order By: Relevance
“…p21 is furthermore transcriptionally inhibited by a Myc-Miz complex [ 102 , 103 ] and activated by Smad/FoxO complexes in response to TGF beta stimulation [ 104 ]. The regulation of p16INK4A, p14/p14ARF/p19ARFArf, and p21 are reviewed in detail elsewhere [ 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: P16ink4a P14arf/p19arf and P21—basic Molecular Mechanismsmentioning
confidence: 99%
“…p21 is furthermore transcriptionally inhibited by a Myc-Miz complex [ 102 , 103 ] and activated by Smad/FoxO complexes in response to TGF beta stimulation [ 104 ]. The regulation of p16INK4A, p14/p14ARF/p19ARFArf, and p21 are reviewed in detail elsewhere [ 105 , 106 , 107 , 108 , 109 , 110 ].…”
Section: P16ink4a P14arf/p19arf and P21—basic Molecular Mechanismsmentioning
confidence: 99%
“…Because p53 plays an important role in driving cell cycle arrest and damage repair in response to DNA damage [13, 21, 28, 45], we asked whether excess cell size causes increased sensitivity to DNA damaging agents, which was recently reported in palbociclibtreated cells [11]. We found that the proliferation of enlarged cells released from G 1 into a low dose of doxorubicin ( Figure 6A-6B ) or camptothecin ( Figure 6C-6D ) is stunted compared to size-constrained cells, indicating that DNA damage sensitivity following prolonged G 1 arrest is a consequence of increased cell size and not the arrest itself.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, DNA replication machinery is not limiting for proliferation in excessively large cells. Because p21—which should repress E2F gene expression through the inhibition of cyclin:Cdk complexes [13]— is elevated in enlarged cells, this suggests that opposing mechanisms drive E2F protein expression. This may be related to the recent observation that Rb concentrations are reduced as cells grow larger [19, 20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBNA-3C has the ability to interfere with intracellular p53-mediated signaling [126]. p53, the transcription factor responsible for tumor suppression, is widely described in the literature both as a cell cycle regulator and as a potent pro-apoptotic agent [127][128][129][130][131][132]. p53 may promote the expression of the pro-apoptotic members of Bcl-2 family [130] The intracellular signaling network dependent on p53 includes Puma [133], Bim [134], Bid [135], Bax [136,137], and Bak [138,139].…”
Section: Ebna-3cmentioning
confidence: 99%